K3 training for the safety of fishermen in Muara Pantuan Village, Anggana District - Maulita, Maulita; Rahmat, Rahmat; Luturmas, Fabiola Bulimasena (Community Empowerment, 2021)
This community service aims to provide occupational safety training (K3) to fishermen in Muara Pantuan Village, Anggana District. Based on the observations, it was found that fishermen do not understand and aware of the implementation of K3 when carrying out their activities. Based on this condition, it can pose a risk that endangers the lives of the fishermen. The activity was carried out on 8-9 July 2021 through the training and demonstrations on the use of safety equipment from the community service teams. In addition, community service teams also provided assistance in the form of safety jackets that can be used during fishing activities at sea. Through this Community Service (PkM), fishermen will be aware of the importance of using K3 tools, especially during activities at sea.